Approach and Management Strategies for Radicular Low Back Pain in Ayurveda: The Classical and Emerging Methods: Life Sciences-Ayurveda - Verma, Piyush; Kanaujia, Shiwangi; Surve, Sakshi; Pathak, Ashutosh Kumar (International Journal of Life Science and Pharma Research, 2024)
Radicular low back pain management in Ayurveda includes oral ayurveda formulations for local applications and systemicpanchakarma procedures. Several practitioners of Ayurveda are also practicing marma therapy. The lacunae in today’s knowledgeare that very less clinical trial evidence can guide ayurveda practitioners in managing this complaint. Due to a lack of documentedevidence and research, these therapies and techniques are not used in mainstream management protocols in large public settings.It makes these therapies inaccessible to the general public. This study aims to review the management methods for radicular lowback pain or sciatica from published resources and to discuss its approach. For this review study, previous published research andarticles on ayurveda and low back pain, sciatica, Ghridhrasi, Katishoola, Katigraha, and Marma therapy have been searched fromstandard databases (PubMed and Science Direct) and relevant books. After a thorough search, 12 papers on standard databaseswere reviewed for this study and incorporated to build up the concept of radicular low back pain management through ayurveda.The study concluded that Ayurveda provides a holistic approach and encompasses various pharmacological and nonpharmacologicalmethods to manage pain and associated disability. Marma therapy can become long-term, cost-effective methodsto tackle this growing problem. Thus, public settings must be equipped rigorously with ayurveda therapy units for radicular lowback pain. Larger scale randomized controlled interventional trials and research needs to be done to evaluate the effect andlimitations of ayurveda therapies (ancient and emerging) for radicular low back pain and develop standard management protocols.